Prediction of the Temperature Behaviour During Friction Stir Welding (FSW) Using HyperworksÂ® - Meyghani, B. (Springer Science and Business Media Deutschland GmbH, 2021)
Fundamentally, heat is needed during friction stir welding (FSW) for joining materials together. This heat is usually produced by friction force and material deformation. Therefore, friction coefficient is a significant factor and in order to increase the efficiency and the quality of the simulated model, there is a need to explore it accurately. However, previous studies used constant values of the friction coefficient resulting in inaccuracy of the model. This paper proposes, a mathematical formulation for predicting temperature dependent values of the friction coefficient using coulomb friction and von Mises yield laws. Then, the friction coefficient values are used to simulate a finite element model. HyperMeshÂ® and HyperViewÂ® solvers have been employed from Altair HyperworksÂ® to simulate the process. The results of the model showed that, the temperature at the shoulder surface is always higher than the pin area, thus the heat generated by shoulder is found to be higher around 60Â â. Furthermore, higher temperature at the advancing side (around 30Â â) was obtained. Finally, the model is verified to show the accuracy of the predicted friction coefficient values and the results of the finite element model. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.